2021
DOI: 10.1200/jco.20.02401
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation in Patients Undergoing Allogeneic Hematopoietic Cell Transplantation

Abstract: PURPOSE To examine the incidence and risk factors for de novo atrial fibrillation (AF) after allogeneic hematopoietic cell transplantation (HCT) and to describe the impact of AF on HCT-related outcomes. METHODS A retrospective cohort study design was used to examine AF and associated outcomes in 487 patients who underwent allogeneic HCT from 2014 to 2016 and to characterize patient- and HCT-related risk factors. A nested case-control study design was used to describe the association between pre-HCT echocardiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…ened in-hospital adverse events, a large portion of which was driven by cardiovascular mortality. 9 The aforementioned trends are reflected in our study which showed greater odds of all-cause mortality and anticipatory cardiac complications including aCHF. Structural T A B L E 2 Summary of total number of events and adjusted odds ratios for in-hospital complications.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…ened in-hospital adverse events, a large portion of which was driven by cardiovascular mortality. 9 The aforementioned trends are reflected in our study which showed greater odds of all-cause mortality and anticipatory cardiac complications including aCHF. Structural T A B L E 2 Summary of total number of events and adjusted odds ratios for in-hospital complications.…”
Section: Resultssupporting
confidence: 53%
“…Atrial arrhythmias are common in hematological malignancies and the presence of arrhythmias in patients undergoing ASCT has previously been associated with increased likelihood of ICU admission, longer median hospital stay, and higher in‐hospital mortality 8 . A retrospective study by Chang et al correlated echocardiographic parameters such as increased left atrial ejection fraction and volume index to the development of AF post‐ASCT; they also noted worsened in‐hospital adverse events, a large portion of which was driven by cardiovascular mortality 9 . The aforementioned trends are reflected in our study which showed greater odds of all‐cause mortality and anticipatory cardiac complications including aCHF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cardiac comorbidity of current anti-tumor therapies may have a tremendous impact on the long-term survival and morbidity of tumor patients, as was most prominently described for anthracycline-induced cardiomyopathy [ 47 ]. Transient cardiac damage during anti-leukemic therapies, as indicated by elevation of cardiac stress or ischemia markers such as N-terminal pro-brain natriuretic peptide (NT-proBNP) and troponin T, as well as arrhythmias, are regularly seen in patients during intensive anti-leukemic therapies [ 48 ]. Therefore, it seems reasonable to complement the careful clinical monitoring of cardiotoxicity in leukemic patients with further characterization of organ-specific side effects and signaling pathways activated by malignancy and/or anti-tumor therapies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac comorbidity of current anti-tumor therapies may have tremendous impact on long-term survival and morbidity of tumor patients as most prominently described for anthracycline-induced cardiomyopathy (14). On the other side transient cardiac damage during anti-leukemic therapies as indicated by elevation of cardiac stress or ischemia markers such as NT-proBNP and troponin T as well as arrhythmias are regularly seen in patients during intensive anti-leukemic therapies (15). It therefore seems reasonable to complement careful clinical monitoring of cardiotoxicity in leukemic patients with further characterization of organ-specific side effects and signaling pathways activated by malignancy and/or anti-tumor therapies in the future.…”
mentioning
confidence: 99%